On the “Atypical” Imperative Verb Form in Manda - Bernander, Rasmus (Studia Orientalia Electronica, 2020)
This paper accounts for the atypical Imperative verb form found in Manda, a Bantu language spoken along the shores of Lake Nyasa in southern Tanzania. Unlike the vast majority of Bantu languages, Manda lacks a reflex of the so called “morphologically specialized” imperative. Instead, Imperatives (as well as other directives) are expressed with the suffixation of a marker of the form -ayi. Based on the form-meaning variation found both language-internally and in comparative data, this study reconstructs the functional and formal pathways of change leading to the highly unusual situation encountered in today’s Manda. The study shows that the Manda Imperative originates from a construction consisting of a reflex of the pre-final morpheme *-a(n)g-, an imperfective marker originally recruited into the directive domain to add pragmatic overtones of emphasis. However, at some point in time the meaning of this erstwhile emphatic construction became neutralized and conventionalized as the regular imperative, while the marker itself became decategorialized and morphophonologically opaque.